2019
DOI: 10.1002/chem.201805478
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Charge‐Transfer in Conjugated Microporous Polymers for Photocatalytic Hydrogen Evolution

Abstract: Bandgap engineering in donor–acceptor conjugated microporous polymers (CMPs) is a potential way to increase the solar‐energy harvesting towards photochemical water splitting. Here, the design and synthesis of a series of donor–acceptor CMPs [tetraphenylethylene (TPE) and 9‐fluorenone (F) as the donor and the acceptor, respectively], F0.1CMP, F0.5CMP, and F2.0CMP, are reported. These CMPs exhibited tunable bandgaps and photocatalytic hydrogen evolution from water. The donor–acceptor CMPs exhibited also intramol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 78 publications
1
44
0
Order By: Relevance
“…The poly(arylene ethynylene)‐type PPCs functionalized with Tröger's base ( S BET =750 m 2 ⋅ g −1 ) were prepared from 1,3,5‐triethynylbenzene and diiodinated Tröger's base monomers through direct step‐growth polymerization performed by means of Sonogashira coupling . The direct copolymerization through Suzuki‐Miyaura coupling and tetrakis(4‐bromophenyl)ethane, 2,7‐dibromo‐9‐fluorenone, and 1,4‐benzene diboronic acid comonomers were used to prepare donor‐acceptor PPCs highly efficient towards hydrogen evolution . In the case of the above‐mentioned PPCs prepared by direct polymerizations, the organometallic or heteroatomic segments of the PPCs served not only as catalytically active centres, but simultaneously participated (as the rigid network struts) in the formation of the porous texture of the PPCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poly(arylene ethynylene)‐type PPCs functionalized with Tröger's base ( S BET =750 m 2 ⋅ g −1 ) were prepared from 1,3,5‐triethynylbenzene and diiodinated Tröger's base monomers through direct step‐growth polymerization performed by means of Sonogashira coupling . The direct copolymerization through Suzuki‐Miyaura coupling and tetrakis(4‐bromophenyl)ethane, 2,7‐dibromo‐9‐fluorenone, and 1,4‐benzene diboronic acid comonomers were used to prepare donor‐acceptor PPCs highly efficient towards hydrogen evolution . In the case of the above‐mentioned PPCs prepared by direct polymerizations, the organometallic or heteroatomic segments of the PPCs served not only as catalytically active centres, but simultaneously participated (as the rigid network struts) in the formation of the porous texture of the PPCs.…”
Section: Introductionmentioning
confidence: 99%
“…[20] The direct copolymerization through Suzuki-Miyaura coupling and tetrakis(4-bromophenyl) ethane, 2,7-dibromo-9-fluorenone, and 1,4-benzene diboronic acid comonomers were used to prepare donor-acceptor PPCs highly efficient towards hydrogen evolution. [21] In the case of the above-mentioned PPCs prepared by direct polymerizations, the organometallic or heteroatomic segments of the PPCs served not only as catalytically active centres, but simultaneously participated (as the rigid network struts) in the formation of the porous texture of the PPCs. This positively influenced the specific surface area of PPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, conjugated organic semiconductors have attracted much attention as photocatalysts for hydrogen generation because of their potential advantages such as flexible molecular structure, tuneable electronic property and band gap. [6][7][8][9][10][11][12] The representative organic polymer photocatalysts mainly include linear conjugated polymers (CPs), [13][14][15][16][17][18][19] graphitic carbon nitrides (g-C 3 N 4 ), 20,21 conjugated microporous polymers (CMPs), [22][23][24][25][26][27] crystalline covalent organic frameworks (COFs), [28][29][30][31][32][33] and covalent triazine-based frameworks (CTFs). [34][35][36][37][38][39] It has been proved that the selectivity of a suitable building block is important to improve the photocatalytic activity of organic polymer photocatalysts, and many studies have demonstrated that dibenzothiophene-S,S-dioxide with strong electron accepting ability is an efficient building block to generate organic polymer photocatalysts with high photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, redox‐active CMPs were also found to be capable of in situ generation and stabilization of metal nanoparticles (NPs), and subsequently, such metal nanoparticle stabilized CMP (NP@CMP) materials have shown significantly improved electrocatalytic activities . Furthermore, organic porous materials have been explored recently as heterogeneous catalysts for the photochemical H 2 evolution reaction . However, improvements in both these processes in a cost‐effective manner are important challenges for the scientific community .…”
Section: Introductionmentioning
confidence: 99%
“…[22,41] Furthermore, organic porousm aterials have been exploredr ecently as heterogeneous catalysts for the photochemical H 2 evolution reaction. [48][49][50][51][52][53][54] However, improvements in both these processes in ac ost-effectivem anner are importantc hallenges for the scientificc ommunity. [55] To the best of our knowledge,C MP materials with bimodal functionality that can catalyze both the electrochemical ORR and the photochemical H 2 evolutionr eactiona re yet to be documented.…”
Section: Introductionmentioning
confidence: 99%